Seminar Edukasi Untuk Meningkatkan Kesadaran Masyarakat terhadap Dampak Pernikahan Dini di Desa Naga Kesiangan - Andika Saputra; M. Wahyu; Widya Amelita Dewi Asri Harahap; Khairan Nur Panggabean; Nadya Kartika; Anggun Salsabila Samosir; Rina Filia Sari (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this education is to increase public awareness, especially among teenagers, of the impacts of early marriage through educational seminars and Service-Learning-based outreach in Naga Kesiangan Village. Early marriage remains a critical issue in Indonesia, often associated with health risks, psychological stress, and limited educational and social opportunities for young people. The Service-Learning approach was chosen because it not only provides knowledge transfer but also actively engages participants in reflection and discussion, ensuring that the learning process is more contextual and sustainable. The method used was Service-Learning, involving 30 teenagers aged 15–19 years, 15 parents, and 5 community leaders who were purposively selected for their direct relevance to the issue. Activities included seminars, small group discussions, interactive question-and-answer sessions, and collective reflection. The results of the activity showed a significant increase in participants’ understanding, from 42% (pre-test) to 81% (post-test). Participants gained a deeper understanding of the health, psychological, social, and educational risks of early marriage and were encouraged to delay marriage by choosing positive alternatives through education and skill development. This program also strengthened the role of families and community leaders as preventive agents by fostering collective awareness and support. Thus, educational seminars integrated with Service-Learning prove to be effective and replicable strategies to prevent early marriage practices, while also empowering communities to build healthier, more resilient generations.